ANALISA PELAKSANAAN PROGRAM PKK DAN DAMPAKNYA TERHADAP KETAHANAN PANGAN KELUARGA DI KELURAHAN KARANGTENGAH, KAPANEWON WONOSARI, KABUPATEN GUNUNGKIDUL - Suindartini; Juliswara, Vibriza (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This research aims to evaluate the implementation of the food security program by the PKK in Karangtengah Subdistrict, Wonosari, Gunungkidul. This research uses a qualitative research method with a case study approach. The results of the research show that the food security program planning by the PKK in Karangtengah Subdistrict has been carried out well. This planning involves various stakeholders and is adapted to the potential and problems that exist in the area. The implementation of the food security program by the PKK in Karangtengah Subdistrict has also gone well. This program has had a positive impact on food security in Karangtengah Subdistrict.